STRATEGI KESANTUNAN BERBAHASA IKLAN GOJEK DAN GRAB - Andi Indah Yulianti; Dwiani Septiana; Hasina Fajrin R. (Kantor Bahasa Provinsi Gorontalo, 2021)
As a business that is engaged in providing services, in its competition, Gojek and Grab cannot be separated from the use of polite language to attract customers. This study aims to determine the form of politeness in the Gojek and Grab commercials. At the same time, the purpose of this study is to describe the form of politeness of the language contained in the Gojek and Grab commercials and find out which of the two big companies are more polite by using the politeness theory of Brown and Levinson, and Leech. This research uses the listening method, and the primary data is taken from Gojek and Grab's latest ad titled GoFood Versi Anak Baru (GojekIndonesia, 2019) and GrabFood Punya 3 Kode yang Bikin Kamu Bahagia. Based on both commercials' analysis, it can be concluded that Grab ads are more polite than Gojek ads. Grab ads are made with utterances that fulfill the politeness maxim and use a positive politeness strategy. Conversely, Gojek Ads use speech that contradicts politeness strategy; that is, speech does not conform to negative politeness strategies by minimizing coercion. In the use of language, the Grab app commercial is polite compared to the Gojek app commercial. However, if it is seen from the possibility of their product promotion's success, Gojek might be superior by showing impoliteness to do polite things.